Randomized controlled trial comparing operative times between standard and robot‐assisted laparoscopic hysterectomy1. Issue 1 (3rd November 2016) - Deimling, Timothy A.; Eldridge, Jennifer L.; Riley, Kristin A.; Kunselman, Allen R.; Harkins, Gerald J.
Abstract: Objective: To compare the operative time between robot‐assisted laparoscopic hysterectomies and standard laparoscopic hysterectomies. Methods: A prospective, randomized controlled trial enrolled women aged 18–80 years attending Penn State Hershey Medical Center between April 23 and October 20, 2014 to undergo hysterectomy. Participants were randomized using a random number generator to undergo either robot‐assisted or standard laparoscopic hysterectomy. The primary outcome was the total operative time (surgeon incision to surgeon stop, including robot docking time, if applicable). Intention‐to‐treat analyses were performed and the operative time was compared between the two treatments for non‐inferiority, defined as a difference in operative time of no longer than 15 minutes. Results: There were 72 patients randomized to each treatment arm. The mean operative time was 73.9 minutes (median 67.0 minutes; interquartile range 59.0–83.0 minutes) in the robot‐assisted hysterectomy group and 74.9 minutes (median 65.5 minutes; interquartile range 57.0–90.5 minutes) in the standard laparoscopic hysterectomy group. The upper bound of the 95% confidence interval of the difference in operative time was 6.6 minutes, below the 15‐minute measure of non‐inferiority. Conclusion: When performed by a surgeon experienced in both techniques, the operative time for robot‐assisted laparoscopic hysterectomy was non‐inferior to that achieved with standard laparoscopic hysterectomy. ClinicalTrials.gov: NCT02118974 Abstract : The operative time of robot‐assisted laparoscopic hysterectomy was non‐inferior to that of standard laparoscopic hysterectomy.